Effect of pressure on the physical properties of magnetorheological fluids - A. Spaggiari; E. Dragoni (Fracture and Structural Integrity)
To date, several applications of magnetorheological (MR) fluids are present in the industrial world, nonetheless system requirements often needs better material properties. In technical literature a previous work shows that MR fluids exhibit a pressure dependency called squeeze strengthen effect. Since a lot of MR fluid based devices are rotary devices, this paper investigates the behaviour of MR fluids under pressure when a rotation is applied to shear the fluid. The system is designed in order to apply both the magnetic field and the pressure and follows a Design of Experiment approach. The experimental apparatus comprises a cylinder in which a piston is used both to apply the pressure and to shear the fluid. The magnetic circuit is designed to provide a nearly constant induction field in the MR fluid. The experimental apparatus measures the torque as a function of the variables considered and the yield shear stress is computed. The analysis of the results shows that there is a positive interaction between magnetic field and pressure, which enhances the MR fluid performances more than twice.